Analisis studi kelayakan bisnis pada industri perbankan syariah di Indonesia: Studi pada PT. Bank BCA Syariah - Putri, Laurina Trisnaning; Amin, Sakinah Maulidah Mastniah; Agustina, Putri Nur Latifah; Salsabilla, Lathifah Zaina; Solekah, Nihayatu Aslamatis (Maliki Interdisciplinary Journal, 2024)
The expansion of Indonesia's Islamic banking sector reflects the public's desire for sharia-compliant financial services. The purpose of this research is to examine the business feasibility study of PT Bank BCA Syariah. The research approach used was a review of the literature and a thorough examination of the internal and external elements affecting BCA Syariah's company. The findings indicate that BCA Syariah has the potential and capability to function. Legal compliance, Islamic product compliance, solid IT support, and a dedication to sustainability are all advantages. Finally, by adhering to Sharia principles and constantly innovating, BCA Syariah is able to achieve positive growth and have a positive impact on the Indonesian economy and society. The findings demonstrated that Bank BCA Syariah has the potential and capability to function. Legal compliance, sharia-compliant products, strong IT support, and a dedication to environmental principles are all advantages. Legal, environmental, marketing, technical and technological, HR management, financial, and AMDAL elements are also analyzed. Bank BCA Syariah is able to generate positive growth and have a positive impact on the economy and Indonesian society because of its adherence to Sharia principles and sustainable innovation.